1997
DOI: 10.1111/j.1752-1688.1997.tb04112.x
|View full text |Cite
|
Sign up to set email alerts
|

IN‐STREAM HABITAT UNIT CLASSIFICATION: INADEQUACIES FOR MONITORING AND SOME CONSEQUENCES FOR MANAGEMENT1

Abstract: Habitat unit classification can be a useful descriptive tool in hierarchical stream classification. However, a critical evaluation reveals that it is applied inappropriately when used to quantify aquatic habitat or channel morphology in an attempt to monitor the response of individual streams to human activities. First, due to the subjectivity of the measure, observer bias seriously compromises repeatability, precision, and transferability of the method. Second, important geomorphic and ecological changes in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 25 publications
3
54
0
1
Order By: Relevance
“…This is performed visually based on recognition of streambed topography, flow patterns, and patterns of spatial bed-material variability. The delineation of geomorphological units may be difficult, particularly for inexperienced operators (Poole et al 1997). Delineation requires training and the results are affected by the stage of flow.…”
Section: Characterization and Delineation Of Geomorphological Unitsmentioning
confidence: 99%
“…This is performed visually based on recognition of streambed topography, flow patterns, and patterns of spatial bed-material variability. The delineation of geomorphological units may be difficult, particularly for inexperienced operators (Poole et al 1997). Delineation requires training and the results are affected by the stage of flow.…”
Section: Characterization and Delineation Of Geomorphological Unitsmentioning
confidence: 99%
“…Classification (the ordering of objects into labelled groups based on common characteristics) has been broadly applied to river channels (Rosgen 1994;Poole, Frissell & Ralph 1997), with more than 40 geomorphically based classification schemes employed or proposed in various parts of the world, based on factors such as channel pattern, gradient, bed material size and sediment load (Kondolf et al . 2003).…”
Section:    :        mentioning
confidence: 99%
“…Previous studies of channel unit-based systems suggested that they were inadequate for monitoring because channel unit identification was subjective and imprecise and hence, the data were biased and highly variable (Roper and Scarnecchia 1996;Poole et al 1997). …”
Section: Discussionmentioning
confidence: 99%